1989
DOI: 10.1111/j.1469-8986.1989.tb01932.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Change in Tone Frequency on the Habituated Orienting Response of the Sleeping Rat

Abstract: EEG arousal and heart rate responses to change in tone frequency following habituation training were studied during slow wave sleep in the rat. Rats were exposed to sequences of 12 tone pulses. Habituation stimuli (trials 1-7) had a frequency of 16 kHz. The frequency of the following (test) trials was changed to either 5, 12, 14, 22, or 40 kHz. Hearing level was held constant for all frequencies. Test trials were repeated five times to study rehabituation. The results indicate that heart rate deceleration is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Johnen (Johnen, 1987;Johnen & Schnitzer, 1989) has shown that adult rats tested during slow-wave sleep do exhibit heart-rate deceleration to a novel auditory stimulus. However, in none of those studies are subjects also tested while awake, making it impossible to assess the effect of behavioral state on the magnitude of the heart-rate response.…”
Section: Discussionmentioning
confidence: 99%
“…Johnen (Johnen, 1987;Johnen & Schnitzer, 1989) has shown that adult rats tested during slow-wave sleep do exhibit heart-rate deceleration to a novel auditory stimulus. However, in none of those studies are subjects also tested while awake, making it impossible to assess the effect of behavioral state on the magnitude of the heart-rate response.…”
Section: Discussionmentioning
confidence: 99%
“…Experiment 2 sought to test this possibility by presenting the subjects used in Experiment 1 with a tone stimulus similar to that used by Kapp et al Although the Experiment 1 rats had already had a substantial amount of experience with the white noise startle stimulus, it was assumed that a new stimulus given in a new context would be sufficiently different to reinstate the habituated heart rate decelerations. Evidence shows that a previously habituated heart rate deceleration to an acoustic stimulus can be re-evoked if the test stimulus is sufficiently different from the habituated stimulus (Campbell & Haroutunian, 1983; Johnen & Schnitzler, 1989).…”
Section: Methodsmentioning
confidence: 99%